Four new Pseudosinella (Collembola: Entomobryidae) from La Rioja, Spain - Benito, José C. Simón; Palacios-Vargas, José G. (Zootaxa, 2008)
Four new species of Pseudosinella from La Rioja, Spain are described and illustrated. They are P. logrognensis sp. nov., P. leivaensis sp. nov., P. gutierrezae sp. nov. and P. torcuatoensis sp. nov., which were found in soils of different field crops. Identification keys are given for some of them, based on the chaetotaxy or the number of eyes, in order to compare the new species with those having 5 + 5 eyes.